Cross-cultural research methods in psychology - Matsumoto, David Ricky, 1959-; Vijver, Fons J. R. van de, 1952- (Cambridge University Press, 2011)
"Cross-cultural research is now an undeniable part of mainstream psychology and has had a major impact on conceptual models of human behavior. Although it is true that the basic principles of social psychological methodology and data analysis are applicable to cross-cultural research, there are a number of issues that are distinct to it, including managing incongruities of language and quantifying cultural response sets in the use of scales. Cross-Cultural Research Methods in Psychology provides state-of-the-art knowledge about the methodological problems that need to be addressed if a researcher is to conduct valid and reliable cross-cultural research. It also offers practical advice and examples of solutions to those problems and is a must-read for any student of culture"--Resumé vydavatele
Keywords: psychologický výzkum; psychologická metodologie; interkulturní psychologie; psychological research; psychological methods; cross-cultural psychology; kolektivní monografie; collective monographs